Prevalence and Imaging Characteristics of Palatine Tonsilloliths Detected by CT in 2,873 Consecutive Patients - Akira Takahashi; Chieko Sugawara; Takaharu Kudoh; Daisuke Uchida; Tetsuya Tamatani; Hirokazu Nagai; Youji Miyamoto (The Scientific World Journal)
Aim. Tonsilloliths are calcified structures that develop in tonsillar crypts. They are commonly detected in daily clinical practice. The prevalence of tonsilloliths was 16 to 24% in previous reports, but it is inconsistent with clinical experience. The aim of this study is to clarify the prevalence, number, and size distribution of tonsilloliths using computed tomography (CT) in a relatively large number of patients. Materials and Methods. We retrospectively reviewed the scans of 2,873 patients referred for CT examinations with regard to tonsilloliths. Results. Palatine tonsilloliths were found in 1,145 out of 2,873 patients (39.9%). The prevalence of tonsilloliths increased with age, and most commonly in patients of ages 50–69. The prevalence in the 30s and younger was statistically lower than in the 40s and older (P < 0.05). The number of tonsilloliths per palatine tonsil ranged from one to 18. The size of the tonsilloliths ranged from 1 to 10 mm. For the patients with multiple CT examinations,　the number of tonsilloliths increased in 51 (3.9%) and decreased in 84 (6.5%) of the tonsils. Conclusions. As palatine tonsilloliths are common conditions, screenings for tonsilloliths during the diagnosis of soft tissue calcifications should be included in routine diagnostic imaging.